Pengaruh Faktor Keuangan terhadap Financial Distress dengan dimoderasi oleh Komite Audit - Anita Evrilianingsih; Annisa Shaffana Amalia (Politeknik Ganesha Medan, 2022)
Research on the company's financial difficulties is very important because it can lead to bankruptcy which will have a bad impact on the country's economy. This study aims to provide empirical evidence about the influence of financial factors, namely operating cash flow per share (OCFS) and current ratio (CR) in predicting financial distress moderated by the expertise of the audit committee. This research is a quantitative study on property & real estate sector listed on the Indonesia Stock Exchange (IDX) in the 2015-2019 period. The number of samples as many as 36 companies from 73 populations was obtained through the purposive sampling technique. This study uses the Moderated Regression Analysis (MRA) method in analyzing the processed data using the SPSS application. The results showed that operating cash flow per share can reduce financial distress while the current ratio has no effect on financial distress. In addition, it was found that the expertise of the audit committee strengthens the relationship between operating cash flow per share and financial distress, but not the relationship between the current ratio and financial distress. This research is useful to provide insight to investor,company’s management, financial institutions, stakeholders and other related parties in future decision making.